Debt Financing dan Equity Financing Pada Profit Expense Ratio Perusahaan Bank Syariah di Indonesia - Adinda Nani Nur Amalia; Dian Indriana Hapsari (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The study aims to determined the effect of the level of debt financing and equity financing on the profit expense ratio in islamic banks. This study uses a quantitative method with a population of 16 companies. The technique used in this study was purposive sampling, in order to obtain a sample of 6 companies with a total of 12 data spanning the 2018-2021 observation years. The test tool used is Multiple Linear Regression Analysis using SPSS 23. The results show that debt financing has no effect on the profit expense ratio. Meanwhile, equity financing has an influence on the profit expense ratio.